Estudio de eficiencia energética en los laboratorios de mecánica industrial y soldadura de la Universidad de las Fuerzas Armadas ESPE sede Latacunga - Aulestia Araujo, Pablo Sebastián (2022)
This project aims to capture the analysis regarding energy efficiency that can be acquired in the laboratories of industrial mechanics and welding of the University of the Armed Forces ESPE headquarters Latacunga through a study of loads placed on the transformer of 100kVA and 75kVA respectively. From this study the objective of this project is to present in a practical way proposals in the reduction of electricity consumption for the institution applying knowledge of efficiency, auditing and considerations to establish optimal energy savings.